The Application of the Guided Composition Method in Writing Arabic Sentences: تطبيق طريقة الإنشاء الموجه في كتابة جمل اللغة العربية - Iqsan, Chairul Razi; Ersa, Muhammad Zulfikar (Al Mihwar: Jurnal Pendidikan Bahasa Arab dan Kebahasaan, 2025)
This study investigates the application of the Guided Composition Method in teaching Arabic sentence writing to second-year students at Ulumuddin Islamic Junior High School, Uteunkot Cunda, Lhokseumawe. The research was motivated by the need to strengthen students’ written expression skills through an instructional approach that facilitates accurate sentence construction in Arabic. A descriptive-analytical design was adopted, employing multiple data collection techniques, including classroom observation, interviews with teachers and students, and analysis of students’ written work following the implementation of the method. The qualitative analysis focused on students’ engagement with the method and the progression of their writing proficiency. Findings revealed notable variation in student responses: while several students demonstrated positive engagement and marked improvement, others encountered difficulties in comprehending certain concepts. The study concludes that the Guided Composition Method constitutes an effective pedagogical strategy when applied with flexible instructional practices that accommodate individual learning differences. Accordingly, the method holds significant potential to enhance students’ proficiency in Arabic writing when integrated into a well-structured teaching framework.